2015
DOI: 10.1111/nmo.12670
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels of lipopolysaccharide and antiflagellin antibodies in patients with diarrhea‐predominant irritable bowel syndrome

Abstract: Our results support the concept that immune reactivity to luminal antigens may have a role in the development of D-IBS. The serum level of antiflagellin antibodies was found to correlate with patients' self-reported anxiety score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 45 publications
(51 reference statements)
3
65
1
6
Order By: Relevance
“…Whether lactulose challenge may impair mucosal barrier function at a tight junction level, without causing ‘mucosal damage’ as measured by iFABP, remains unclear. Intravenous infusion of LPS in healthy volunteers triggers visceral hypersensitivity with characteristics similar to those observed in IBS patients (25), and elevated plasma levels of LPS were associated with IBS (IBS-D) in a recent study (26). A separate study demonstrated elevated serum immunoglobulin A against LPS in patients with fatigue (27), a condition often linked to IBS (28).…”
Section: Discussionmentioning
confidence: 81%
“…Whether lactulose challenge may impair mucosal barrier function at a tight junction level, without causing ‘mucosal damage’ as measured by iFABP, remains unclear. Intravenous infusion of LPS in healthy volunteers triggers visceral hypersensitivity with characteristics similar to those observed in IBS patients (25), and elevated plasma levels of LPS were associated with IBS (IBS-D) in a recent study (26). A separate study demonstrated elevated serum immunoglobulin A against LPS in patients with fatigue (27), a condition often linked to IBS (28).…”
Section: Discussionmentioning
confidence: 81%
“…Evidence of bacterial translocation in IBS is also provided by higher peripheral levels of LPS as well as higher concentrations of anti-flagellin antibodies [86] . Moreover, Escherichia coli LPS-induced IL-6 secretion is elevated in IBS, indicating an enhanced response against Gram-negative bacteria in this disorder [82] .…”
Section: Gut Dysbiosis and Bacterial Translocation As A Link Between mentioning
confidence: 99%
“…Diarrhea, constipation and intestinal inflammation are the main symptoms of the patients with IBD and IBS [1112]. Clinical and epidemiological studies indicate that the inflammation is found from the jejunum to the rectum in both IBS and IBD [1314151617]. Diarrhea is the common symptoms of IBD; IBS may have constipation-predominant symptom or diarrhea-predominant symptom [181920].…”
Section: Introductionmentioning
confidence: 99%